Feasibility of HPV self-sampling pathway in Kathmandu Valley, Nepal using a human-centred design approach. Issue 3 (1st January 2022) - Shrestha, Swastika; Thapa, Saki; Sims, Paul; Ardelean, Andreea; Basu, Anamika; Caws, Maxine; Gurung, Suman Chandra; Holdsworth, Gillian
Abstract: Cervical cancer is preventable and curable yet causes almost 2000 deaths in Nepali women each year. The present study aims to explore the feasibility and acceptability of a self-sampling-based approach for cervical cancer screening in urban and peri-urban Nepal and develop pathways for self-sampling using a co-design methodology. An iterative design approach was applied. Semi-structured in-depth interviews were conducted with 30 healthy women and four women who had had a prior cancer diagnosis on topics which included: sexual and reproductive health knowledge and human papillomavirus (HPV); use of the internet/social media platforms; their views regarding acceptability and usability of the self-sampling kit and the proposed user journey. Data collection was done between December 2020 and January 2021. Seven medical experts were also interviewed to explore the current service configuration for cervical cancer screening in Nepal. Knowledge regarding HPV and its association with cervical cancer was absent for the majority of participants. Although 70% ( n = 21/30) had purchased items online previously, there was a general lack of trust in online shopping. Half of the women ( n = 17/30; 56.7%) expressed a willingness to self-sample and provided recommendations to improve the clarity of the instructions. The proposed user journey was considered feasible in the urban area. There is a clear unmet need for information about HPV and alternative cervical screening options in Nepal. An online pathway for self-sampling service delivery to urban women is feasible but will need to be optimally designed to address barriers such as confidence in self-sampling and trust in online purchasing.